The Dirt Powered Fuel Cell (DPFC) - RAMLI, MUHAMMAD NAIM; Sahari, Norain (Progress in Engineering Application and Technology, 2025)
The Dirt Powered Fuel Cell (DPFC) project explores soil-based microbial fuel cells using electroactive microbes to generate electricity sustainably. Responding to the challenge of improving clean energy technology, the study investigates how electrode configurations (packed vs. planar) and materials (graphite, carbon cloth, aluminum mesh) impact performance. The objectives were to optimize electrode design for maximum electricity output and develop a system capable of powering a DC load. The methodology involved constructing three test chambers which are Chambers A, B, and C with varying materials and configurations, monitoring voltage, current density, and power density over four days. Quantitative findings revealed that Chamber C, with a planar electrode arrangement combining carbon cloth and aluminum mesh, achieved the highest metrics voltage of 602 mV, the current density of 2.95 mA/ and power density of 1,777 µW/. Finally, a series‑parallel assembly of 24 such fuel cells produced 8 V at 50 mA, sufficient to light a 5 V bulb and indicate practical viability. The study concludes that judicious selection of electrode materials and configurations substantially enhances DPFC output, demonstrating its promise as an eco-friendly small-scale energy source.